(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Although methods are available to treat proliferative diabetic retinopathy (PDR), 30% of cases progress, which is an indication for vitrectomy. Purpose: To investigate the ophthalmoscopic and morphological features of epiretinal membranes (ERMs) in patients with PDR depending on the dose of preoperative intravitreal aflibercept (PIA). Material and Methods: Seventy-five patients (75 eyes) with PDR and the presence of fibrovascular ERM with a marked proliferative component were involved in the study. Patients were divided into three groups: eyes of group 1 or control group (31 eyes) received vitrectomy without PIA; group 2 (17 eyes), PIA 1.0 mg; and group 3 (27 eyes), PIA 2.0 mg. We performed a histological study on specimens of fibrovascular ERMs surgically obtained from patients to determine the microscopic features of these membranes. Results: There was ophthalmoscopic and microscopic evidence that aflibercept pretreatment in vitrectomy for PDR resulted in fibrosis of the ERM. The extent of fibrosis of the ERM and obliteration of newly formed blood vessels in the ERM depended on the dose of PIA. Complete obliteration of newly formed blood vessels in the ERM was observed as early as day 3 after 2.0-mg intravitreal aflibercept injection compared to day 5 after 1.0-mg intravitreal aflibercept injection. Pretreatment with 1.0-mg intravitreal aflibercept in vitrectomy for PDR reduced the probability of complications associated with ERM contraction, worsening of the tractional component and the development of a retinal break.